At Her Majesty's Pleasure: Criminal Insanity in 19th-Century Britain - Evans, Catherine L. (History compass, 2016)
Criminal insanity cases tried in common law courts in the 19th century attracted the sustained attention of doctors, lawyers, government officials and members of the public. This intense interest was due, in part, to the drama of these cases. However, criminal insanity and the criminally insane also prompted experts and others to contemplate intractable, metaphysical questions about the limits of sanity, the existence of free will and the justification of judicial punishment. This essay argues that, while scholars working in the field of what might be called ‘forensic psychiatry studies’ are acutely conscious of the many ways in which the history of criminal insanity intersects with broader histories of the mind sciences, law and the self, criminal insanity remains largely, and regrettably, tangential to these broader literatures. The essay describes some new directions in the scholarship on criminal insanity that promise to enrich forensic psychiatry studies and also, it is hoped, related fields.